Inclusive cultural dakwah practices from the perspective of islamic education: A study of sedulur pembarep creative space, samiranan village, kandangan district - Dea Puji Saputri; Mia Surya Fatzila; Nishvi Launi Hasna Kamalia; Zazilatul Zaziroh; Muhammad Laduna Mazura Yusuf; Ulfiana Afifah; Husna Nashihin (At Turots: Jurnal Pendidikan Islam, 2024)
The background of this research is based on the lack of culturally inclusive da'wah education in society, so that a da'wah model is needed that can reach the community, both socially and culturally and is carried out in a dialogue. Such as the one carried out at Sedulur Pembarep Creative Space (SPCS), Samiranan Village, Kandangan District. This research aims to examine the practice of culturally inclusive da'wah from an Islamic education perspective, analyze the impact of culturally inclusive da'wah practices in developing the character of tolerance in society, and understand the challenges of SPCS in developing culturally inclusive da'wah practices from an Islamic education perspective. This research uses a phenomenological approach. The type of research employed is field research using qualitative methods. Data collection techniques include observation, interviews, and documentation. Data sources consist of primary and secondary data. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. Data validity was strengthened through triangulation of sources, techniques, and time. Research on culturally inclusive da'wah practices at SPCS is manifested in spiritual performing arts, cross-identity cultural discussions, and educational activities that combine Islamic educational values with local cultural symbols. The impacts of da'wah practices include increased public awareness of the importance of tolerance, strengthening social character, and creating a welcoming da'wah space for diversity. However, internal challenges include financial support, while external challenges include community misconceptions and limited human resources in managing technology and information.